Narcotics Abuse by Children and its Prevention - Nursariani Simatupang; Faisal Faisal (Universitas Muhammadiyah Sumatera Utara, 2022)
Drug abuse is carried out not only by adults, but also by adolescents. Teenagers who should have been educated for the betterment of this nation, also fell into the circle of drug abuse. Drug abuse has very fatal consequences in adolescents. Among teenagers who use narcotics do not even continue their education. In fact, education is a very important thing for them, for the achievement of their goals and future. Teenagers do not understand that drug abuse has negative repercussions. For this reason, it is necessary to prevent it, so that adolescents avoid drug abuse. This research is a normative juridical research, which is research that conducts an assessment of library materials. The data source used is secondary data. Data collection tools used are documentation studies, with qualitative analysis techniques. In general, the impact of drug abuse can be seen physically, psychically, and socially. Some of the efforts that can be made to prevent drug abuse are increasing the role of the family, religious guidance, and education on the dangers of narcotics